2007
DOI: 10.1182/blood-2007-05-089003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for MPL W515L/K mutations in hematopoietic stem cells in primitive myelofibrosis

Abstract: IntroductionThe BCR-ABL-negative chronic myeloproliferative disorders (MPDs) include polycythemia vera (PV), essential thrombocytosis (ET), and primitive myelofibrosis (PMF). 1 These disorders are hematologic malignancies characterized by a clonal proliferation of one or several myeloid lineages. 2 PV, ET, PMF, and chronic myeloid leukemia (CML), defined as the classical MPDs, are considered to arise from the transformation of a multipotent hematopoietic stem cell. [3][4][5][6] However, the stem cell origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 46 publications
1
75
0
3
Order By: Relevance
“…Chaligne et al 19 have shown that MPLW515K mutations are already present in early hematopoietic stem and progenitor cells, including SCID-repopulating cells. For this reason and based on the experience with the JAK2V617F, it might well be expected that MPLW515L would become positive in the case of malignant relapse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chaligne et al 19 have shown that MPLW515K mutations are already present in early hematopoietic stem and progenitor cells, including SCID-repopulating cells. For this reason and based on the experience with the JAK2V617F, it might well be expected that MPLW515L would become positive in the case of malignant relapse.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 To detect MPLW515L/K mutations, genotyping techniques using allele-specific PCR were first used with qualitative or semiquantitative results and a 3-5% sensitivity level. 6,19 Pyrosequencing is a quantitative technique resulting in a sensitivity of only 5%. 20,21 Melting curve analysis using LightCycler assay was also reported to be sensitive for mutant allele burden of at least 5%.…”
Section: Discussionmentioning
confidence: 99%
“…1,[19][20][21][22][23][24][25][26] Using cell clonality assays including X-chromosome-linked polymorphisms, FISH and specific mutations (Ras, JAK2V617F and MplW515L), several myeloid lineages (granulocytes, erythrocytes, platelets and monocytes) have been shown to be involved by the malignant process in the majority of patients with PV, PMF and ET; and the lymphoid cells in a subpopulation of these patients. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Although MCs originate from the same progenitor cells, as granulocytes, erythrocytes, platelets and monocytes, whether MCs are also involved by the malignant process in PV, PMF and ET has not been previously explored. In this study, we established MC cultures from CD34 þ cells purified from PB of patients with PV and PMF, and examined the presence of JAK2V617F and/or MplW515L mutations as well as chromosomal abnormalities in the HCMCs.…”
Section: Discussionmentioning
confidence: 99%
“…27 The JAK2V617F mutation is present in the CD34 þ cells as well as cells belonging to several myeloid lineages (granulocytes, erythrocytes and monocytes) in the majority of patients with PV and the lymphoid cells of a sub-population of PV patients. [28][29][30][31] Hu et al 32 and Chaligné et al 33 have reported that the MplW515L/K mutations are present in granulocytes, monocytes, platelets, natural killer cells as well as B-and Tlymphocytes in patients with PMF, indicating that the MplW515L/K mutations originate in a progenitor cell common to both myeloid and lymphoid cells. 32,33 Despite being one of the myeloid lineages, the involvement of MCs by the malignant process in PV, ET and PMF has not been reported earlier.…”
Section: Introductionmentioning
confidence: 99%
“…1 MPDs are hematological diseases characterized by a clonal proliferation of one or several myeloid lineages 2 arising from the transformation of a multipotent hematopoietic stem cell by an oncogenic event such as Bcr-abl fusion protein kinase, mutated Janus kinase JAK2 V617F or thrombopoietin receptor (TPO-R) MPL W515L that induces constitutive signaling. [3][4][5] However, approximately 40% of patients with ET and PMF do not present such mutations, [6][7][8][9][10][11] and genetic analysis is still under progress to elucidate the responsible oncogenic events.…”
Section: Introductionmentioning
confidence: 99%